2013
DOI: 10.1200/jop.2012.000738
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Colorectal Cancer Care Among Veterans: Analysis of Treatment Wait Times at Veterans Affairs Medical Centers

Abstract: Purpose: Timeliness of cancer treatment is an important aspect of health care quality. Veterans Affairs Medical Centers (VAMCs) are expected to treat a growing number of patients with cancer. Our objectives were to examine treatment times from diagnosis to first-course therapy for patients with colon and rectal cancers and assess factors associated with prolonged wait times. Methods:From the VA Central Cancer Registry, patients who underwent colon or rectal resection for cancer from 1998 to 2008 were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(15 reference statements)
1
13
0
Order By: Relevance
“… 45 Similarly, Merkow et al examined time from CRC diagnosis to first-course therapy, and found that time to first treatment increased over the study period (1998–2008) for both colon and rectal cancers. 46 …”
Section: Resultsmentioning
confidence: 99%
“… 45 Similarly, Merkow et al examined time from CRC diagnosis to first-course therapy, and found that time to first treatment increased over the study period (1998–2008) for both colon and rectal cancers. 46 …”
Section: Resultsmentioning
confidence: 99%
“…This study was performed within the VA system, which has well-documented long wait times for surgery. 65,66 These added clinic spots could play an important role in a larger effort to improve access to surgical services and decrease wait times. Although the VA system has garnered the most scrutiny, the problem of limited access to specialty care is widespread throughout the health care system, 65,67,68 providing ample opportunity for creative telemedicine solutions.…”
Section: Discussionmentioning
confidence: 99%
“…on veterans have focused on racial disparities in cancer care at U.S. Department of Veterans Affairs medical centers (VAMCs) (Zullig et al, 2013), treatment wait times at VAMCs (Merkow et al, 2013), navigating veterans with an abnormal prostate cancer screening test (Simon et al, 2013), and demographic variables related to treatment outcomes (Landrum et al, 2012;Wang et al, 2012). Patient-centered care in VAMCs is believed to be able to "reduce variability in cancer care" of veterans (L. Hoffman-Hogg, personal communication, April 11, 2013).…”
mentioning
confidence: 99%